Systematic classification of maternal and fetal intervention‐related complications following open fetal myelomeningocele repair – results from a large prospective cohort. (30th November 2020) - Vonzun, L; Kahr, MK; Noll, F; Mazzone, L; Moehrlen, U; Meuli, M; Hüsler, M; Krähenmann, F; Zimmermann, R; Ochsenbein‐Kölble, N
Abstract : Objective: To systematically categorise all maternal and fetal intervention‐related complications after open fetal myelomeningocele (fMMC) repair of the first 124 cases operated at the Zurich Centre for Fetal Diagnosis and Therapy. Design: A prospective cohort study. Setting: Single centre. Population: Mothers and fetuses after fMMC repair. Methods: Between 2010 and 2019, we collected and entered all maternal complications following fMMC repair into the Clavien–Dindo classification. For fetal complications, a classification system based on the Medical Dictionary for Regulatory Activities terminology of Adverse Events was used including the preterm definitions of the World Health Organization. Main outcome measures: Systematic classification of maternal and fetal complications following fMMC repair. Results: Gestational ages at surgery and birth were 25.0 ± 0.8 and 35.4 ± 2.0 weeks, respectively. In 17% of all cases, no maternal complications occurred. Maternal intervention‐related complications were observed as follows: 69% grade 1, 36% grade 2, 25% grade 3, 6% grade 4 and 0% grade 5. In 34%, no fetal complications were noted; however, 43% of the fetuses developed a grade 1, 14% a grade 2, 8% a grade 3, 2% a grade 4 and 2% a grade 5 complication. Conclusion: This study raises awareness of complications following open fMMC repair; 6% of mothers and 2% of fetuses experienced a severe complication (grade 4) and perinatal death rate of 2% was observed (grade 5). These data are useful for prenatal counselling, they help to improve the system of fetal surgical care, and they allow benchmarking with other centres as well as comparison with fetoscopic approaches. Tweetable abstract: Systematic classification of all maternal and fetal intervention‐related complications following open fMMC repair. Tweetable abstract: Systematic classification of all maternal and fetal intervention‐related complications following open fMMC repair.